Technology, the environment and social change - Noble, Patricia (SALALM Secretariat [Albuquerque]US, 1995)
Focuses on aspects such as the environmental and society today; new technology for communication: video; new technology for information management; chinese immigrant communities in Central America and the Caribbean; Cuban bibliography; and, the Hispanic Division of the Library of Congress.